2019
DOI: 10.1186/s12879-019-3821-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the mechanism underlying treatment failure for Salmonella Paratyphi A infection using next-generation sequencing – a case report

Abstract: Background Salmonella is a notorious pathogen that causes gastroenteritis in humans and the emergence of resistance to third-generation cephalosporins and azithromycin have raised concern. There has been rare case of Salmonella Paratyphi A infection accompanied by spondylitis. Here, we report a case of initial antibiotic treatment failure in a Korean man with Salmonella Paratyphi A infection and conducted next-generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…He presented with backache and fevers and had failure of therapy with azithromycin. Patient responded well to ciprofloxacin and cefotaxime combination as evident by improvement in backache and decline of ESR [27].…”
Section: Discussionmentioning
confidence: 93%
“…He presented with backache and fevers and had failure of therapy with azithromycin. Patient responded well to ciprofloxacin and cefotaxime combination as evident by improvement in backache and decline of ESR [27].…”
Section: Discussionmentioning
confidence: 93%
“…These percentages were like those found in this study. The presence of Salmonella strains resistant to quinolones in foods, especially those used for treatment in humans, such as nalidixic acid and ciprofloxacin, is worrying because when its use becomes necessary for the treatment of serious infections it can increase the risk of failure (Park et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although antimicrobials are not indicated in most cases of salmonellosis in humans, its use becomes necessary in severe cases of systemic infections (Boxstael et al 2012, WHO 2018. However, the antimicrobials' lack of susceptibility increases the risk of treatment failures (Park et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Escherichia coli Nissle 1917 (EcN1917), a commercialised and well-characterised therapeutic with over a century-long history of human use [8], was used as the model probiotic while Salmonella Typhimurium, a widespread gastrointestinal pathogen with increasing outbreaks of drug-resistant infections [9] was used to establish a gut infection of the larval model. This study demonstrated that the route of probiotic administration significantly impacts its protective effects and should be considered when screening for probiotics in G. mellonella .…”
Section: Introductionmentioning
confidence: 99%